Modelling and Simulation of 4 DOF Robotic Arm for an Automated Roselle Tea Processing Plant Using Solidwoks and Matlab Simulik. Issue 2 (December 2017) - Adeyeri, M.K.; Ayodeji, S.P.; Olasanoye, O.
Abstract: Modelling of 4 degree of freedom (4 DOF) of robotic arm for roselle tea process plant is being discussed. The design takes into account by calculating the forward and inverse kinematic of this robotic arm motion. The material was analyzed using computer software that calculated the finite element of linear stress analysis of each mechanical components of robotic arm. Besides that, the loads exerted on the robotic arm were also calculated to ensure the mechanical components of the robotic arm is not damaged during operation. The system implementation and optimization was carried out in MATLAB/ Simulink environment. Finite element analysis (FEA), time and motion study were carried out to evaluate the performance of the designed model using Solid Works software. Solid Works, MATLAB/Simulink and Robo Analyzer software packages were used to simulate the virtual robotic arm to analyze and evaluate the performance of the robotic arm. Results show that the robotic arm frame made of aluminum is capable and rigid enough to carry the maximum payload. The maximum equivalent stress induced and displacement are 64.0952 N/mm 2 and 2.796 mm respectively. Also, the robotic arm reached height was found to be 1850 mm with total mass of 33.1 kg; volume of 8.11x 10 -3 m 3 and total surface area of 1.7 m 2 .